Evidence in criminal proceedings amid jurisprudential contradictions: illicit evidence, procedural preclusion, and evidentiary freedom - Valdez Marrou, Alex Antonio (2025)
This article delves into the complex interaction between illicit evidence, procedural preclusion, and evidentiary freedom within the Peruvian legal system, through an analysis of how these facets interact and often contradict each other under the current jurisprudential framework. Beginning with the principle of contradiction, the article highlights its fundamental role in ensuring a fair and equitable trial, allowing parties to know, discuss, and challenge the evidence and arguments against them. This dynamic becomes particularly critical when illicit evidence is involved, where the right to defense may be compromised. The principle of immediacy also plays a crucial role by fostering a direct relationship between the judge and the evidence. This principle is challenged by the presence of illicit evidence, as the judge must balance the need to gain a clear view of the facts with preserving the integrity of the judicial process. Exploring the constitutional right to present evidence, the article considers how this essential right is affected by restrictions on the admissibility of illicit evidence. The tension between the right to present evidence and the exclusion of improperly obtained evidence reflects a complex balance between the search for truth and respect for procedural rights. Procedural preclusion introduces another layer of complexity by outlining specific procedural stages that may limit or enable the presentation of evidence. It examines how these temporal restrictions can impact the handling of illicit evidence, potentially affecting both the defense and the prosecution. The section on evidentiary freedom addresses the scope and limits of this freedom within the Peruvian legal framework, highlighting how it allows for a variety of forms in presenting evidence, while also being restricted by the illegality in obtaining certain pieces of evidence. Finally, the assessment of illicit evidence presents a particular challenge in balancing the right to a fair trial with the need to maintain the integrity of the process. The article discusses the implications of using illicit evidence and highlights cases and jurisprudential decisions that illustrate these tensions. This comprehensive analysis not only exposes the contradictions and challenges present in Peruvian jurisprudence but also underscores the need for a balanced legal framework that respects fundamental rights and upholds the integrity of the judicial process.